PARTNER CITIES: HISTORICAL AND LEGAL ASPECTS OF INTERNATIONAL COOPERATION - Олег ПЕТРИК (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article is devoted to the study of the historical context of the cities’ development as subjects of international relations, their evolutionary transformation from political and security unions, through political and religious unions to large agglomerations capable of conducting independent international activities, taking into account their own socio-economic, cultural and educational interests of their residents. Using an interdisciplinary approach that combines historical, legal, political science, and management disciplines, the author has revealed the multifaceted use of such concepts as «partner cities», «twin cities», «municipal cooperation», «decentralized cooperation of cities» etc., which proves that their use as synonymous definitions indicating a non-governmental, horizontal international level of cooperation between individual local actors is not sufficiently regulated. The study outlined the criteria for selecting a partner city. The historical way of the formation of global and regional international organizations and associations of municipalities, which developed recommendations for in-depth cooperation between cities of different political systems to exchange experience, deepening of cooperation in the environment of modern management in the context of urbanization, is highlighted. It is proved that such initiatives are based on intercultural cooperation, the foundations of the international and national law, which strengthens the reputation and foreign policy integration strategies of the state as a whole. It has been found that often in the process of decentralization, localization, and manifestation of their own subjectivity, cities are more effective and faster in making decisions, establishing international forms of cooperation, and implementing the most important projects.